2019
DOI: 10.1002/med.21597
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein‐associated phospholipase A2: The story continues

Abstract: Inflammation is thought to play an important role in the pathogenesis of vascular diseases. Lipoprotein‐associated phospholipase A2 (Lp‐PLA2) mediates vascular inflammation through the regulation of lipid metabolism in blood, thus, it has been extensively investigated to identify its role in vascular inflammation‐related diseases, mainly atherosclerosis. Although darapladib, the most advanced Lp‐PLA2 inhibitor, failed to meet the primary endpoints of two large phase III trials in atherosclerosis patients cotre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
146
0
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 131 publications
(149 citation statements)
references
References 270 publications
(736 reference statements)
0
146
0
3
Order By: Relevance
“…With the stimulation of INF-α/β/γ and 5-HT2R, PLA activity increases as well (Kurrasch-Orbaugh 2003;Wu et al, 1994). Conversely, PLA2 deactivates in response to glutamine and oxidants (Huang et al, 2020;.…”
Section: Membrane Phospholipidsmentioning
confidence: 99%
“…With the stimulation of INF-α/β/γ and 5-HT2R, PLA activity increases as well (Kurrasch-Orbaugh 2003;Wu et al, 1994). Conversely, PLA2 deactivates in response to glutamine and oxidants (Huang et al, 2020;.…”
Section: Membrane Phospholipidsmentioning
confidence: 99%
“…Approximately 80% of Lp-PLA2 circulates bound to LDL, whereas the other 20% is bound to HDL and very low-density lipoprotein (VLDL) (31). Lp-PLA2 can hydrolyze oxPL at the surface of LDL, which produces a variety of cytokines, adhesion factors, and promotes the formation of atherosclerotic plaques (32). Meanwhile, histopathological examinations have shown that Lp-PLA2 is highly expressed in the late necrotic core of atheromatous plaque, suggesting that it is involved in the formation and development of vulnerable atherosclerotic plaques (33).…”
Section: Discussionmentioning
confidence: 99%
“…Besides, it contributed to the pathogenesis of atherosclerosis [31] and mediation of inflammation [29,32]. Moreover, it could mediate the vasculitis through regulating the metabolism of blood fat [33]. To our best knowledge, rare studies have been focused on the roles of Lp-PLA2 in the WMH.…”
Section: Moreover No Correlation Was Noticed Between Serum Lp-pla2 Amentioning
confidence: 99%